2016
DOI: 10.1155/2016/3989721
|View full text |Cite
|
Sign up to set email alerts
|

Some Risk Factors of Chronic Functional Constipation Identified in a Pediatric Population Sample from Romania

Abstract: We conducted an observational study over a 1-year period, including 234 children aged 4–18 years and their caregivers and a matching control group. 60.73% of the children from the study group were males. Average age for the onset of constipation was 26.39 months. The frequency of defecation was 1/4.59 days (1/1.13 days in the control group). 38.49% of the patients in the sample group had a positive family history of functional constipation. The majority of children with functional constipation come from single… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

5
23
2

Year Published

2018
2018
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 21 publications
(32 citation statements)
references
References 37 publications
5
23
2
Order By: Relevance
“…Similar observations were made by Pashankar et al in their study in which prevalence of obesity was significantly higher in constipated children (22.4%) compared with control children (11.7%). 8 A 44% prevalence of overweight in constipated children was observed in the study by Misra et al 9 A statistically significant difference was observed between groups regarding obesity/overweight and constipation in a study by Olaru et al 10 A lesser incidence of overweight (19.2%), and obesity (6.7%) were observed in children with functional constipation the study by Koppen done at Columbia. 11 This lesser incidence is probably due to the regional variation in the prevalence of overweight and obesity.…”
Section: Discussionmentioning
confidence: 91%
“…Similar observations were made by Pashankar et al in their study in which prevalence of obesity was significantly higher in constipated children (22.4%) compared with control children (11.7%). 8 A 44% prevalence of overweight in constipated children was observed in the study by Misra et al 9 A statistically significant difference was observed between groups regarding obesity/overweight and constipation in a study by Olaru et al 10 A lesser incidence of overweight (19.2%), and obesity (6.7%) were observed in children with functional constipation the study by Koppen done at Columbia. 11 This lesser incidence is probably due to the regional variation in the prevalence of overweight and obesity.…”
Section: Discussionmentioning
confidence: 91%
“…Metabolic syndrome or family history of T2DM seems to increase the risk for NAFLD [55,56] Chronic functional constipation [57] Small intestinal bacterial overgrowth (SIBO) SIBO was found in 37.6% of overweight group. Obese children with SIBO have an increased risk for developing NAFLD.…”
Section: Discussionmentioning
confidence: 99%
“…Corroborating these results, Shau et al [7] and Olaru et al [28] found that the frequent consumption of fast food and inadequate eating habits are associated with constipation [27]. Other authors [7,28,29] suggest that the consumption of foods with high sugar, trans fat, sodium levels, and the inadequate intake of fruits and vegetables favor the increase in prevalence.…”
Section: Markersmentioning
confidence: 95%